Prediction of the sound reduction index of clay hollow brick walls. Issue 2 (June 2020) - Granzotto, Nicola; Di Bella, Antonino; Piana, Edoardo Alessio
Clay hollow brick walls are still popular in building industry, but the prediction of their sound insulation properties is not straightforward due to their inhomogeneous and anisotropic characteristics. In this article, a classic approach has been used to determine the sound transmission coefficient of brick walls, assuming an orthotropic behaviour and deriving the mechanical and dynamic characteristics from datasheet information. Different types of walls with horizontal and vertical mortar joints have been analysed. Experimental measurements of the sound reduction index carried out according to ISO 10140-2 standard have been performed, and the resulting values are compared with the predictions in the proposed model. It was found that the sound reduction index can be fairly predicted in the low-frequency range and it is correctly predicted in the mass law region, whereas in the high-frequency range the inner block structure is responsible for a loss of performance which is difficult to predict with the analytical methods.